The Pselaphinae (Coleoptera: Staphylinidae) of New Caledonia and Loyalty Islands. II. Revision of the tribe Tyrini Reitter, 1882 - Hlaváč, Peter (Zootaxa, 2009)
The tribe Tyrini of New Caledonia is revised. The genus Anagonus Fauvel is redescribed based on the study of the type species, A. fracticornis Fauvel. Two new species of Anagonus are also described, A. spinipalpis sp. nov. and A. breviscapus sp. nov. Two new genera: Caledonogonus gen. nov., with two new species, C. loebli sp. nov. and C. pilosus sp. nov., and Paranagonus gen. nov. with one new species, P. excavatus sp. nov., are described. Keys to genera and species are provided.